2010
DOI: 10.1021/pr100678k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals a “Poised Quiescence” Cellular State after Triggering the DNA Replication Origin Activation Checkpoint

Abstract: An origin activation checkpoint has recently been discovered in the G1 phase of the mitotic cell cycle, which can be triggered by loss of DNA replication initiation factors such as the Cdc7 kinase. Insufficient levels of Cdc7 activate cell cycle arrest in normal cells, whereas cancer cells appear to lack this checkpoint response, do not arrest, and proceed with an abortive S phase, leading to cell death. The differential response between normal and tumor cells at this checkpoint has led to widespread interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 75 publications
2
30
0
Order By: Relevance
“…Joint MS data processing for all OAC and OXS biological samples using MaxQuant (version 1.5.3.28) 18,19 with a common UniProt human proteome set (ftp://ftp.uniprot.org/pub/databases/uniprot/current_release/knowledgebase/proteomes/ downloaded 01-25-2013) was performed as described previously. 8,9,11 The acceptance of proteins as adequately quantified, which was based on minimum numbers of SILAC ratio counts, at least two replicates and MaxQuant Significance B scores, as well as the selection of the significant sets of proteins (401-set, 49-set, see text), is described in detail in the Supplementary Text.…”
Section: Imr90 (Atcc Ccl-186) a Human Diploid Fibroblast Adherent Cementioning
confidence: 99%
See 1 more Smart Citation
“…Joint MS data processing for all OAC and OXS biological samples using MaxQuant (version 1.5.3.28) 18,19 with a common UniProt human proteome set (ftp://ftp.uniprot.org/pub/databases/uniprot/current_release/knowledgebase/proteomes/ downloaded 01-25-2013) was performed as described previously. 8,9,11 The acceptance of proteins as adequately quantified, which was based on minimum numbers of SILAC ratio counts, at least two replicates and MaxQuant Significance B scores, as well as the selection of the significant sets of proteins (401-set, 49-set, see text), is described in detail in the Supplementary Text.…”
Section: Imr90 (Atcc Ccl-186) a Human Diploid Fibroblast Adherent Cementioning
confidence: 99%
“…The connection to MCM5 is of interest because suppression of the CDC7 kinase (for OAC) induces cell cycle arrest at the origin activation checkpoint for DNA replication by reducing phosphorylation of the MCM complex. 8,10 The data contains clear evidence that analyses based only on changes in total abundance of proteins may miss important functional relationships. other interaction is substantial ( ; for co-expression/binding respectively) and the other pathway SET-FTH1-HMOX1 is also substantial (Fig.…”
Section: 5c An Extended Pcna / Set / Ptma / Hmox1 Nuclear Controlmentioning
confidence: 99%
“…To elucidate the mechanisms involved in regulation of this checkpoint, we have previously used a combination of cell biology, transcriptomics and a global quantitative proteomics approach. 5,22 Specifically, we triggered the activation of this novel checkpoint by RNAi depletion of CDC7 in IMR90 normal human diploid fibroblasts. We have shown that this checkpoint-activated cell cycle arrest is coordinated by the transcription factor FOXO3a, which undergoes subcellular redistribution to the nucleus for activation of the p53-p21 axis and for upregulation of p15-INK4B and p21.…”
Section: Introductionmentioning
confidence: 99%
“…Response to TLR3 activation was defined by altered levels of protein abundance in human SV40-fibroblasts when stimulated with poly(I:C) (used as TLR3 agonist 69 ) and was measured by SILAC/MS 1214 monitoring of heavy/light isotope labelling ratios for peptides from proteins of stimulated/unstimulated cells (Figure 1A). …”
Section: Resultsmentioning
confidence: 99%